Preservice Physical Education Teachers’ Preferences of Mosston’s and Ashworth’s Teaching Styles - Constantinides, Panos; Antoniades, Orestis (An Overview of Literature, Language and Education Research Vol. 7, 2024)
Physical education is an important part of the school curriculum designed to help kids develop motor skills, knowledge and behaviors of a healthy active lifestyle, physical fitness, sportsmanship, self-efficacy, and emotional stability. Having Mosston’s (1966) and Mosston’s & Ashworth’s (2002, 2008) “Spectrum of Teaching Styles” as a guiding tool, research on teaching styles in physical education has been rising for over 50 years. The spectrum offers a variety of teaching styles to be used by physical education teachers, which fall into two broad categories: the rather teacher-centered reproduction styles and the rather student-centered production styles. This paper is part of a larger-scale study for teaching effectiveness, in which teaching components were examined. The purpose of this study was to investigate preservice physical education teachers’ preferences of teaching styles during student teaching in public schools. For that purpose, a convenient sample of 16 students of a private University in Cyprus, participated in this study. Data collection took place in the Spring 2022 semester. All students took Physical Education Pedagogy Class I and then Physical Education Pedagogy Class II, which included student placement in secondary public schools for student teaching purposes. Students were taught Mosston’s and Ashworth’s Spectrum of Teaching Styles in-depth, with various examples, teaching style video analysis and workshops, to ensure that all possessed the knowledge and skills to incorporate any teaching style in their teaching. Each student was placed in three different secondary schools, to ensure that he/she would be able to teach in any school context with various circumstances. The investigators observed all students according to the schedule that was prepared in collaboration with school principals and physical education teachers in the participating schools. The investigators took field notes for the application of the teaching styles, as well as for the school context. In addition, informal interviews were conducted with students after each class. Student teachers were given their first field experience, to be able to apply their knowledge and developed skills in school settings. Data were analyzed via constant comparison and analytic induction methods. Student teachers in this study have used teaching styles from the reproduction style in all parts of the class, with the exception of the final assessment where most of them have used production teaching styles. The results revealed three important themes: a) Student teachers preferred mostly teaching styles from the reproduction category, such as the command and the practice style, especially during warm-up or children’s practice time, b) Student teachers incorporated teaching styles from the production category during the introduction or final assessment of the class, such as the guided discovery or the convergent discovery styles and c) There were times during practice, when some students used a mixture of teaching styles, jumping from one style to the other, according to the activity that would follow. The results demonstrated that preservice teachers prefer the utilization of reproduction teaching styles over production teaching styles. Their personal beliefs seem to impact the usage of any style. In addition, discipline, coaching experience, time management, the school context and the content to be taught were factors affecting their preferences, usually in favor of the reproduction teaching styles. However, they should be encouraged to use production teaching styles as well in their teaching, as a means to help children develop in all domains of learning: psychomotor, cognitive and affective. Perhaps, asking preservice teachers to incorporate teaching styles only from the product category in one of their student teaching classes, would help them feel more confident towards that and would allow for more children-centered classes. Students’ practice in schools may need to be re-examined so that preservice teachers will get the opportunity to use teaching styles from both clusters, to better prepare students for the teaching challenges of the 21st century.